Life Cycle Assessment of Sugar Industry Supply Chain: A Comprehensive Analysis of Environmental Impacts: Penilaian Siklus Hidup Rantai Pasokan Industri Gula: Analisis Komprehensif Dampak Lingkungan - Atikha Sidhi Cahyana; Iis Sugiarti; Inggit Marodiah; Intan Rohma Nurmalasari (Academia Open, 2023)
This scientific article aims to address the pressing issue of food wastage, known as "mubazir pangan," in Indonesia and its adverse effects on society, economy, and the environment. Focusing on the sugar industry, the study utilizes Life Cycle Assessment (LCA) to comprehensively analyze the environmental impacts of each process in the Supply Chain Management (SCM). Data collection involves literature studies, raw material usage, production, and product distribution. The LCA reveals significant greenhouse gas emissions, acidification, and eutrophication in the supply chain activities. The results shed light on the need for optimal handling of food wastage, proposing alternative improvements derived from expert interviews at PT. Pabrik Gula. Through Analytical Network Process, the best improvement alternatives are identified to mitigate the industry's impacts. The findings contribute to sustainable practices and environmental conservation in the sugar industry, providing valuable insights for related professionals and stakeholders. Highlight: The study addresses the pressing issue of food wastage in Indonesia and its adverse social, economic, and environmental impacts, emphasizing the need for effective handling and reduction strategies. The research identifies the factors contributing to food wastage and explores their interconnections, aiming for a comprehensive approach to manage food wastage. Using Life Cycle Assessment (LCA), the study analyzes the environmental impacts of the sugar industry's Supply Chain Management (SCM), highlighting significant greenhouse gas emissions, acidification, and eutrophication in various stages. Keyword: Food Wastage, Supply Chain Management, Environmental Impacts, Life Cycle Assessment, Sugar Industry